Molecular studies of Southeast asian woody bamboos (Poaceae: bambusoideae: bambuseae): perspectives in reticulate evolution, phylogenetic relationships and classification / Goh Wei Lim - Goh, Wei Lim (2012)
This study seeks to better understand the phylogenetic relationships of SE Asian woody bamboos belonging to the Paleotropical alliance of the Bambuseae tribe because, apart from a clearly circumscribed Melocanninae, other subtribes (Bambusinae, Racemobambosinae) are not yet clearly demarcated and a number of genera are of uncertain affiliation. The definition of key Bambusinae genera, such as Bambusa (itself with a contentious scheme of subgenera), Dendrocalamus and Gigantochloa is problematic because of morphological overlaps and it is unclear how these mainly erect-suberect bamboos are related to a suite of SE Asian climbing genera, including Dinochloa, Holttumochloa, Kinabaluchloa, Maclurochloa, Mullerochloa, Neololeba, Racemobambos, Soejatmia, Sphaerobambos and Temburongia, many of which have been contentiously placed in Bambusa sensu lato in the past. This study utilized DNA sequence data for a nuclear gene region (Granule Bound Starch Synthase, GBSSI) and 3 chloroplast regions (rps16-trnQ, trnC-rpoB and trnD-T intergenic spacers) for 35 species (representing 5 genera) of erect-suberect Bambusinae, 13 species (10 genera) of climbing bamboos, and 3 Melocanninae species. The phylogenetic analyses recovered six major lineages within the ingroup: (1) the BDG complex (Bambusa, Dendrocalamus, Gigantochloa, Maclurochloa, Phuphanochloa, Thyrsostachys and Soejatmia), (2) the Holttumochloa-Kinabaluchloa clade, which is sister to the BDG complex, (3) the Dinochloa-Mullerochloa-Neololeba-Sphaerobambos (DMNS) clade, (4) the Racemobambos clade, (5) Temburongia simplex, and (6) the Melocanninae clade. Significant incongruence between cpDNA and GBSSI topologies indicates widespread reticulate evolution within the BDG complex in the past, which could account for its taxonomic complexities. This is corroborated by demonstration of an existing natural hybridization between Dendrocalamus pendulus and Gigantochloa scortechinii, where GBSSI haplotypes of the hybrid were highly similar to the species-specific GBSSI sequences of the parental species. The extensive introgressive hybridization in the BDG complex was not detected among the other climbing bamboo lineages, suggesting that the BDG complex and the climbing bamboo lineages are of different subtribes. Overall, this study suggests that the Bambusinae should be delimited by only the BDG complex and the climbing bamboo lineages are distinct from the Bambusinae. Equivocal relationships among the DMNS clade, the Racemobambos clade and T. simplex do not permit clear subtribal recognition for these three clades. The Bambusinae is centred in mainland SE Asia, with decreasing representation towards, and a solitary representative in, Australia. In contrast, the present-day geographical distribution of the DMNS clade suggests that this clade could be of Australasian origin, and the subsequent diversification within this clade could have occurred with dispersal towards SE Asia. Other details of the phylogenetic results variously indicate vicariance across the S China Sea (Kinabaluchloa spp.) and the New Guinea–Sulawesi–Borneo–S Philippines pathway as a dispersal corridor between Australia and SE Asia (DMNS clade). These results, together with findings from other published studies, contribute important indications that past introgression, reticulate evolution and ploidy increases could have been a significant feature in the development of the several woody bamboo lineages.